Management of Immature Cataract and Islamic View of the Disease - Ahmad, Ahmad (Journal La Medihealtico, 2024)
Cataracts are the leading cause of blindness in the world. According to the WHO, there are an estimated 39 million blind people in the world and half of them are caused by cataracts. This report presents the case of a 65-year-old male patient with complaints of blurred vision in the right eye since 5 years ago, the complaints were felt in both eyes but felt heavier in the right eye.Physical examination of the eyes found that the lens of the right eye was cloudy. Visus in the right eye was 1/300 and in the left eye was 20/63. There was partial clouding of the right lens. Then the patient was given cendo lyters eye drops 3 times a day 1 drop and the recommended surgical therapy was phacoemulcification.